Assessing Emotions of Teaching Assistants in Inclusive Education - Yang, Lan; Hsu, Chia-Ling; Ye, Tianfang; Sin, Kuen Fung (Frontiers in Psychology, 2022)
Although there is an increasing body of studies on assessing teacher emotions in mainstream education, there is a lack of appropriate measurement tools to evaluate the emotions of teaching assistants (TA) who need to take care of students with a range of special educational needs (SEN). This study tested the generalisability of the 24-item Teacher Emotion Inventory (TEI, Yang et al., 2021) among 204 teaching assistants in inclusive education of Hong Kong. We conducted both confirmatory factor analysis (CFA) and Rasch analysis to test the within-network validity of the TEI. For the between-network validity, we examined the relationships between TAs' emotions and their attitude towards inclusive education. The Rasch analysis supported the scale’s dimensionality and item fit statistics. The CFA supported the five-factor solution of the TEI. The results also showed statistically significant correlations between positive emotions (joy, love) and TAs' attitudes towards inclusive education. Correlations between negative emotions (anxiety, anger, and stress) appear negative/almost uncorrelated. The results supported TEI is a useful tool to assess the emotions of TAs who play a pivotal role in helping SEN students and who are more likely to face emotional challenges than those who might not need to educate SEN students. Implications of this study to enrich the current scope of research on understanding teacher emotions across educational levels and settings are discussed.